PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN - Fatyandri, Adi Neka; Wenny; Muchsinati, Evi Silvana (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to explore the relationship between various human resource practices, such as recruitment and selection, training and development, compensation, performance appraisal, and succession planning, with employee performance in the current economic and organizational context. Using a literature review, this study will formulate hypotheses about the relationships between these factors. The research method will involve analyzing previous studies and developing a research model to test the formulated hypotheses. It is expected that the results of this study will provide a deeper understanding of how HR practices can affect employee performance, as well as offer new insights for practitioners and academics in the field of HR. The practical benefits of this research include providing valuable contributions to organizations in designing effective HR strategies and offering useful guidance for relevant stakeholders. This study aims to analyze the relationship between human resource practices and employee performance. The findings are expected to provide insights for developing effective HR strategies.